How Much Do Students Matter? Applying the Oaxaca Decomposition to Explain Determinants of Adequate Yearly Progress. - Krieg, John M.; Storer, Paul (Contemporary Economic Policy, 2006)
The federal government and many state governments have recently passed legislation that punishes school districts for not showing consistent improvement in standardized test scores. This article measures the extent to which school performance reflects student characteristics. After splitting schools in the state of Washington based on adequate yearly progress, the authors find that an overwhelming percentage of the difference between high-and low-performing schools is explained by characteristics beyond the control of school administrators. Thus legislation designed to penalize poorly performing schools may hurt students who are most in need of academic aid. (JEL 12) Reprinted by permission of the publisher.